Sądowa kontrola prawa do informacji publicznej - Jaśkowska, Małgorzata (Kwartalnik Prawa Publicznego, 2013)
By analyzing the issues concerning the administrative court control over the access to public information, the author highlights that when tackling those issues one must take into consideration both the right to access public information, and the legal boundaries of the public and private classified information. The author discusses certain cases connected to the issues of personal data protection, right to privacy, enterprise secret or protection of non-public information. It is also stressed in this work that protection of the non-public information ensues after a material requirement (the nature of information) and formal requirement (action taken to classify such information) have been met – however, both those elements should be evaluated by the administrative courts under the control procedure regarding the refusal to share public information. Maintaining effectiveness of such control procedure requires additional legislative amendments, among others in respect of reformatory action to be taken by the administrative courts.